Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1177/875687050402300303
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Measure for Social Goals of Inclusion

Abstract: Teachers in rural areas are finding that more and more special needs children are being included in their K-12 classrooms to comply with the mandate for a free and appropriate public education even in isolated small school systems. For students with mild intellectual disabilities (MID) this placement is meant to accomplish both the academic and the social goals in their individualized educational programs (IEP). Measuring progress in the achievement of social goals is less straightforward than measuring academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
12
1
2
Order By: Relevance
“…Nota and associates (2010) explained the lack of differences in self-efficacy beliefs in male and female persons with ID by the fact that school and extra scholastic activities for individuals with ID were rarely differentiated by gender, and thus girls and boys with ID mainly had similar experiences. The results of this research which refer to individual qualities in the sense of relatedness domain, are consistent with the findings of other authors indicating that in children and adolescents with ID gender was not significantly related to peer acceptance and relations (Smoot, 2004;Wendelborg & Kvello, 2010) or social skills (Adeniyi & Omigbodun, 2016;Heiman & Margalit, 1998). This is further supported by empirical findings that academic competence, physical appearance and behavior problems had more influence on the status of persons with ID in their peer group than gender (Baydik & Bakkaloğlu, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nota and associates (2010) explained the lack of differences in self-efficacy beliefs in male and female persons with ID by the fact that school and extra scholastic activities for individuals with ID were rarely differentiated by gender, and thus girls and boys with ID mainly had similar experiences. The results of this research which refer to individual qualities in the sense of relatedness domain, are consistent with the findings of other authors indicating that in children and adolescents with ID gender was not significantly related to peer acceptance and relations (Smoot, 2004;Wendelborg & Kvello, 2010) or social skills (Adeniyi & Omigbodun, 2016;Heiman & Margalit, 1998). This is further supported by empirical findings that academic competence, physical appearance and behavior problems had more influence on the status of persons with ID in their peer group than gender (Baydik & Bakkaloğlu, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…On the basis of a systematic review of literature in this area, Verdonschot and colleagues (2009) concluded that persons with ID had less contact with family and friends, and that their social networks were relatively small, mainly consisting of persons with ID. Furthermore, research on peer interactions of students with ID in regular schools indicated that they socialized with peers with ID more than with TD peers (Cutts & Sigafoos, 2001), that they were poorly accepted by their peers (Smoot, 2004), that they were less popular, had fewer friends, and were rarely included in friend groups (Koster et al, 2010). A lower level of tolerance of differences was determined in adolescents with mild ID, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Kaynaştırma eğitimine devam eden öğrencilerin normal gelişen akranları tarafından sosyal kabul düzeyini inceleyen araştırmalar ise özel gereksinimli öğrencilerin akranları tarafından dışlandığını ortaya koymuştur (Akçamete ve Ceber, 1999;Baydık ve Bakkaloğlu, 2009;Göl, 2014;Manetti, Schneider ve Siperstein, 2001;Smoot, 2004;Şahbaz, 2004;Vuran, 2005). Bu araştırmalardan birinde kaynaştırma uygulamasına devam eden ve kaynaştırmaya aday gösterilen öğrencilerin sosyometrik konumları incelenmiş ve öğrencilerin yarısından fazlasının akranları tarafından reddedildiği, düşük sosyal tercih puanları aldıkları görülmüştür (Vuran, 2005).…”
Section: Introductionunclassified
“…However, school‐age children with disabilities have a less positive assessment of their social belonging than that of their peers with no disabilities (Hogan et al. 2000; Watson & Keith 2002), they are less socially preferred among their peers (Cambra & Silvestre 2003; Smoot 2003), and they participate less in social and curriculum activities at school (Simeonsson et al. 2001; Eriksson et al.…”
Section: Introductionmentioning
confidence: 99%